2019
DOI: 10.3390/cells8020088
|View full text |Cite
|
Sign up to set email alerts
|

Hutchinson-Gilford Progeria Syndrome—Current Status and Prospects for Gene Therapy Treatment

Abstract: Hutchinson-Gilford progeria syndrome (HGPS) is one of the most severe disorders among laminopathies—a heterogeneous group of genetic diseases with a molecular background based on mutations in the LMNA gene and genes coding for interacting proteins. HGPS is characterized by the presence of aging-associated symptoms, including lack of subcutaneous fat, alopecia, swollen veins, growth retardation, age spots, joint contractures, osteoporosis, cardiovascular pathology, and death due to heart attacks and strokes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 146 publications
(197 reference statements)
0
46
0
2
Order By: Relevance
“…To understand the molecular mechanism and cellular pathophysiology of HGPS and the effects of drug treatment, mainly cell culture and animal model studies are conducted (Piekarowicz et al 2019;Vidak and Foisner 2016). For cell culture studies, mostly the tissues from HGPS patients (primary culture/cell lines) and mouse embryonic fibroblasts (MEFs) from progeroid mice are used (Piekarowicz et al 2019), and a number of markers based on the phenotype of HGPS cells are observed.…”
Section: Contemporary and Emerging Disease Models To Study Hgpsmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the molecular mechanism and cellular pathophysiology of HGPS and the effects of drug treatment, mainly cell culture and animal model studies are conducted (Piekarowicz et al 2019;Vidak and Foisner 2016). For cell culture studies, mostly the tissues from HGPS patients (primary culture/cell lines) and mouse embryonic fibroblasts (MEFs) from progeroid mice are used (Piekarowicz et al 2019), and a number of markers based on the phenotype of HGPS cells are observed.…”
Section: Contemporary and Emerging Disease Models To Study Hgpsmentioning
confidence: 99%
“…To understand the molecular mechanism and cellular pathophysiology of HGPS and the effects of drug treatment, mainly cell culture and animal model studies are conducted (Piekarowicz et al 2019;Vidak and Foisner 2016). For cell culture studies, mostly the tissues from HGPS patients (primary culture/cell lines) and mouse embryonic fibroblasts (MEFs) from progeroid mice are used (Piekarowicz et al 2019), and a number of markers based on the phenotype of HGPS cells are observed. The biomarkers include nuclear blebbing, cellular senescence (measured by the status of βgalactosidase), progerin level, ratio of progerin to lamin A/C/B, mitochondrial function, nuclear trafficking, cellular proliferation, ROS (reactive oxygen species) generation and antioxidant status, epigenetic markers (viz.…”
Section: Contemporary and Emerging Disease Models To Study Hgpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional typical features include cardiovascular disease and stroke, atherosclerosis, hip dislocations, and other abnormalities. Individuals with HGPS die of heart disease at an average age of 13 years, with a range of about 8 to 21 years (Piekarowicz, Machowska, Dzianisava, & Rzepecki, ; Ullrich & Gordon, ). Mutant lamins trigger nuclear lamina abnormalities, make the nuclear envelope unstable, and progressively damages the nucleus, in turn making cells more likely to die prematurely (Prokocimer, Barkan, & Gruenbaum, ).…”
Section: Npcs Nuclear Lamina and Oxidative Stressmentioning
confidence: 99%
“…In HGPS cells, however, the wild-type LMNA gene is also expressed. Thus, a combination of lamin A/C and progerin is detectable at the nuclear level, although the molecular reason for such a phenomenon is not well understood (Yang et al, 2008;Piekarowicz et al, 2019). Because of the laminopathy created by progerin, HGPS patients show growth retardation early in their childhood, along with other symptoms of physiological aging: loss of hair, skin thinning, joint rigidity, osteoporosis, and so on.…”
Section: Introductionmentioning
confidence: 99%